Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s12967-015-0705-8
|View full text |Cite
|
Sign up to set email alerts
|

Cotton rat immune responses to virus-like particles containing the pre-fusion form of respiratory syncytial virus fusion protein

Abstract: BackgroundVirus-like particles (VLPs) based on Newcastle disease virus (NDV) core proteins, M and NP, and containing two chimera proteins, F/F and H/G, composed of the respiratory syncytial virus (RSV) fusion protein (F) and glycoprotein (G) ectodomains fused to the transmembrane and cytoplasmic domains of the NDV F and HN proteins, respectively, stimulate durable, protective anti-RSV neutralizing antibodies in mice. Furthermore, immunization of mice with a VLP containing a F/F chimera protein with modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 53 publications
4
35
0
Order By: Relevance
“…and Anderson, 2006). VLP derived from hepatitis B virus (Ye et al, 2013), Newcastle disease virus (Schmidt et al, 2014;Cullen et al, 2015), and parvovirus (Gilbert et al, 2004(Gilbert et al, , 2006 have been shown to be suitable candidates for the expression of foreign epitopes. In the present study, we demonstrated that the recombinant CPV VP2 linked to MERS RBD results in self-assembly into sVLP which display the RBD on the surface, and showed that this vaccine candidate is able to induce robust B-and T-cell responses in mice.…”
Section: Discussionmentioning
confidence: 99%
“…and Anderson, 2006). VLP derived from hepatitis B virus (Ye et al, 2013), Newcastle disease virus (Schmidt et al, 2014;Cullen et al, 2015), and parvovirus (Gilbert et al, 2004(Gilbert et al, , 2006 have been shown to be suitable candidates for the expression of foreign epitopes. In the present study, we demonstrated that the recombinant CPV VP2 linked to MERS RBD results in self-assembly into sVLP which display the RBD on the surface, and showed that this vaccine candidate is able to induce robust B-and T-cell responses in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The purified VLPs were inoculated i.m. in either mice [87] or cotton rats [88], and these animals elicited a serum neutralizing antibody response and were protected against an hRSV challenge. Thus, immunization with pre-fusion F, either as a subunit vaccine or incorporated to recombinant viruses or VLPs, seems to be a promising approach for hRSV vaccine development.…”
Section: Antigenicity and Immunogenicity Of The Hrsv F Glycoproteinmentioning
confidence: 99%
“…Interestingly, animals previously infected and then challenged with RSV had undetectable viral loads in the nose. Hence, intranasal immunization with VLPs may lead to better stimulation of mucosal immune responses and greater protection, compared to other routes of immunization (Cullen et al, 2015).…”
Section: Rats and Guinea Pigs As Models Of Human Nasal Diseasesmentioning
confidence: 99%